2021
DOI: 10.1186/s13045-021-01066-6
|View full text |Cite
|
Sign up to set email alerts
|

HNRNPA2B1 promotes multiple myeloma progression by increasing AKT3 expression via m6A-dependent stabilization of ILF3 mRNA

Abstract: N6-methyladenosine (m6A) modification is the most prevalent modification in eukaryotic RNAs while accumulating studies suggest that m6A aberrant expression plays an important role in cancer. HNRNPA2B1 is a m6A reader which binds to nascent RNA and thus affects a perplexing array of RNA metabolism exquisitely. Despite unveiled facets that HNRNPA2B1 is deregulated in several tumors and facilitates tumor growth, a clear role of HNRNPA2B1 in multiple myeloma (MM) remains elusive. Herein, we analyzed the function a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 10 publications
2
82
1
Order By: Relevance
“…Dali et al (22) observed that YTHDF1-deficient mice presented an enhanced CD8+ T cell infiltration level and the improved therapeutic efficacy of PD-L1 checkpoint inhibitor. However, in MM, very few studies also have revealed the involvement of m6A-related genes in oncogenesis and progression at single gene level (23)(24)(25)(26). Research focusing on the systematic cognition of the role of m6A in the prognosis and immune microenvironment of MM is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Dali et al (22) observed that YTHDF1-deficient mice presented an enhanced CD8+ T cell infiltration level and the improved therapeutic efficacy of PD-L1 checkpoint inhibitor. However, in MM, very few studies also have revealed the involvement of m6A-related genes in oncogenesis and progression at single gene level (23)(24)(25)(26). Research focusing on the systematic cognition of the role of m6A in the prognosis and immune microenvironment of MM is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…As referred above, m6A methylation is the widely popular modification in approximately 100 types of chemical modifications, and m6A modification has made significant contribution to the cancers progression. For example, as a crucial mA "reader," YTHDF1 aggravated the progression of cervical cancer through mA‐mediated up‐regulation of RANBP2, 24 HNRNPA2B1 induced multiple myeloma development by mediating ILF3 mRNA stabilization in a m6A‐dependent manner, 25 and METTL14 inhibited the tumor metastasis of hepatocellular carcinoma via modifying the m6A methylation of GFR/PI3K/AKT 26 . As a crucial m6A methylase, METTL3 has been indicated to involve in cancers progression via mediating cancer‐related proteins methylation level.…”
Section: Discussionmentioning
confidence: 99%
“…Author details 1 Nanjing Hospital of Chinese Medicine affiliated to Nanjing University of Chinese Medicine, Nanjing, China. 2 School of Medicine and Holistic Integrative Medicine, Nanjing University of Chinese Medicine, 138 Xianlin Road, Nanjing 210023, China. 3 Shanghai Unicar-Therapy Bio-Medicine Technology Co., Ltd, Shanghai, China.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Multiple myeloma (MM) is still an incurable hematological malignancy, as most of MM patients eventually relapse or become refractory [ 1 , 2 ]. Strikingly, the CAR-T cell therapy has achieved satisfactory efficacy in patients with relapsed or refractory MM in recent years [ 3 ].…”
mentioning
confidence: 99%